Clinical nursing skills & techniques - Perry, Anne Griffin; Perry, Anne Griffin; Potter, Patricia Ann.; Ostendorf, Wendy (St. Louis, Mo. : Elsevier, 2014)
Over 200 basic, intermediate, and advanced nursing skills and procedures.
Includes Index.
Keywords: Nursing Care -- methods -- Handbooks; Clinical Medicine -- methods -- Handbooks; Evidence-Based Nursing -- methods -- Handbooks; Nursing -- Handbooks, manuals, etc; Clinical medicine -- Handbooks, manuals, etc